Improvement of the Survival of Human Autologous Fat Transplantation by Adipose-Derived Stem-Cells-Assisted Lipotransfer Combined with bFGF - Aimei Jiang; Ming Li; Wenjing Duan; Yilong Dong; Yanmei Wang (The Scientific World Journal)
Adipose-derived stem cells (ASCs) transplanted along with autologous adipose tissue may improve fat graft survival; however, the efficacy of ASCs has been diluted by low vascularization. This study was designed to test the hypothesis that basic fibroblast growth factor (bFGF) may improve the effects of ASCs because it owns the property to boost angiogenesis. In the present study, human fat tissues were mixed with ASCs, ASCs plus 100 U bFGF, or medium as the control and then injected subcutaneously into immunologically compromised nude mice for 12 weeks. Our findings demonstrated that mixture with the ASCs significantly increased the weight and volume of the fat grafts compared to control grafts, and histological analysis revealed that both ASCs and ASCs plus bFGF grafts consisted predominantly of adipose tissue and had significantly less fibrosis but greater microvascular density compared with control and also grafts mixed with ASCs had a high expression of angiogenic factors. More importantly, the bFGF treated fat grafts shown elevate in survival, vascularization, and angiogenic factors expression when compared with the grafts that received ASCs alone. These results indicated that bFGF together with ASCs can enhance the efficacy of autologous fat transplantation and increase blood vessel generation involved in the benefits from bFGF.